2013
DOI: 10.1371/journal.pone.0063993
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic Analysis of a Tertiary Relict Plant, Extreme Xerophyte Reaumuria soongorica to Identify Genes Related to Drought Adaptation

Abstract: Background Reaumuria soongorica is an extreme xerophyte shrub widely distributed in the desert regions including sand dune, Gobi and marginal loess of central Asia which plays a crucial role to sustain and restore fragile desert ecosystems. However, due to the lacking of the genomic sequences, studies on R. soongorica had mainly limited in physiological responses to drought stress. Here, a deep transcriptomic sequencing of R. soongorica will facilitate molecular functional studies and pave the path to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 76 publications
(83 reference statements)
11
52
0
Order By: Relevance
“…Very low precipitation and high temperatures characterize the growing season in ACA, and there are substantial environmental differences between different regions (Chen et al., 2011; Hu et al., 2014). Although these environmental conditions are unfavorable for plant growth, R. soongarica is widespread in these areas (Liu et al., 1982; Shi et al., 2013). According to our data, the leaf area of this species was less than 0.15 cm 2 , which was smaller than that of most species in the world (Diaz et al., 2016; Wright et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Very low precipitation and high temperatures characterize the growing season in ACA, and there are substantial environmental differences between different regions (Chen et al., 2011; Hu et al., 2014). Although these environmental conditions are unfavorable for plant growth, R. soongarica is widespread in these areas (Liu et al., 1982; Shi et al., 2013). According to our data, the leaf area of this species was less than 0.15 cm 2 , which was smaller than that of most species in the world (Diaz et al., 2016; Wright et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, control of phenylpropanoid biosynthesis is complex and plays a significant role in pathogen resistance, anthocyanin biogenesis, and pharmacology (Jimene and Riguera 1994). In this transcriptome study, we identified most of the catabolic genes associated with phenylpropanoid synthesis, demonstrating an understanding of the precise pathway in plants (Shi et al 2013). Genetic, molecular, and biochemical evidence suggests that synthesis and catabolism of phenylpropanoid amino acids are regulated by previously undescribed coordinated mechanisms (Burkhard et al 2001;Grabherr et al 2011).…”
Section: Differentially Expressed Unigenes In Phenylpropanoid Biosyntmentioning
confidence: 72%
“…Also, 32 unigenes had identity to genes involved in ABA-dependent, while 8 unigenes had homology to some genes involved in ABA-independent pathways of drought tolerance. There was a 7.96% of unigenes that did not match any homologous genes in the known plant species [84]. Another study identified 1325 DEGs, including 379 upregulated DEGs and 946 downregulated DEGs under drought stress.…”
Section: Findings Of Novel Genes In Native Plants From Arid Land Areasmentioning
confidence: 99%